A General and Mild Copper(I)‐Catalyzed Three‐Component Reaction of Cyanamides, Amines, and Diaryliodonium Triflates. Issue 14 (27th April 2016) - Li, Jihui; Wang, Hongxing; Hou, Yifeng; Yu, Weiguang; Xu, Shuying; Zhang, Yucang
Abstract: A highly efficient copper‐catalyzed three‐component reaction of cyanamides, amines, and diaryliodonium triflates was developed for the synthesis of guanidines. The mild reaction accommodates both aromatic and aliphatic amines and provides the products in good yields with good functional group tolerance. Moreover, it was demonstrated that C–H activation of the arenes could be realized for the direct preparation of guanidines. Abstract : A Cu‐catalyzed three‐component reaction of cyanamides, amines, and diaryliodoniums is established for the synthesis of guanidines under mild reaction conditions. Guanidines are easily prepared in high yields with broad functional group compatibility. Moreover, C–H activation of the arenes is also realized to make guanidines directly through a one‐pot, two‐step reaction from cyanamides and amines.